Qinwen Baidu decoction for sepsis: A protocol for a systematic review and meta-analysis - Wang, Ping (Medicine (Baltimore), 2019)
BACKGROUND: Sepsis is the most common critical illness in the clinic, with a high incidence and mortality. Qingwen Baidu decoction (QWBDD) has been widely applied in the treatment of sepsis, however, there is no systematic review or meta-analysis of QWBDD in the treatment of sepsis. Hence, we provide a protocol of systematic review and meta-analysis to evaluate the efficacy and safety of QWBDD in the treatment of sepsis. METHODS: The databases including Cochrane Library, PubMed, Embase, Web of Science, Cochrane Clinical Trial Database, World Health Organization International Clinical Trial Registration Platform, CNKI, CBM, VIP, and WanFang Database will be searched from the time when the respective databases were established to January 2019. All randomized controlled trials (RTCs) published in Chinese and English assessing QWBDD for sepsis will be included. Continuity data are expressed as mean difference (MD) or standard mean difference (SMD), and dichotomous data is expressed as relative risk. Analyses will be performed by using RevMan V.5.3.5 software. RESULTS: This study will provide high-quality synthesis of current evidence of QWBDD in the treatment of sepsis from the following aspects, including 28-day mortality, mean arterial pressure (MAP), blood lactate, procalcitonin (PCT), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), hypersensitive C-reactive protein (hs-CRP), acute physiology and chronic health score (APACHE-II), intensive care unit stay, mean hospital stay, mechanical ventilation time, etc. CONCLUSION: Our systematic review will provide evidence for judging whether QWBDD is an effective intervention for sepsis. PROSPERO REGISTRATION NUMBER: PROSPERO CRD 42019123078.